A RESEARCH ON THE SOCIALLY RESPONSIBLE HUMAN RESOURCE MANAGEMENT IN SERBIA - Berber, Nemanja; Slavić, Agneš; Leković, Bojan (International Journal of Economic Practice and Policy, 2020)
Corporate social responsibility (CSR) and sustainable development are concepts that at their core deal with the socially responsible behavior of economic and political actors, i.e. balancing economic, social and environmental goals. CSR is linked to all aspects of management, especially Human Resource Management (HRM). HRM occupies a special place in the area of social responsibility because it refers to people who are engaged in the organization and who are considered to be one of the most important resources of any organization. The aim of the paper is to investigate the relationship between CSR and sustainable development, on the one hand and HRM, on the other. The subject of the paper covers the link between the concept of CSR, sustainable development, and HRM, based on empirical analysis of corporate data from the Republic of Serbia. The research methodology includes theoretical research of the available literature and data, as well as analysis of empirical data on CSR, sustainable development and HRM, based on the CRANET database for Serbia. Descriptive statistics, Pearson’s Chi-square test, and t-test were used for the data processing.